Food products, the WTO dispute settlement system and trade remedies - Bianchi, Eduardo (Instituto Interamericano de Cooperación para la Agricultura, 2021)
One of the Uruguay Round’s more notable achievements was the establishment of the WTO Dispute Settlement System, considered as the “Jewel in the Crown” of the WTO. When the Uruguay Round negotiations were initiated in 1986, there was a growing consensus that the original GATT dispute settlement system was ineffective. Compliance was a key failing of the old system; GATT contracting countries either blocked or simply ignored the findings of panels. The GATT’s consensus rule meant any party—including the potential respondent in a trade dispute who might be accused of wrongdoing—could block not only rulings but even the initiation of an inquiry. Thus, third-party intermediation was often not possible to resolve trade frictions (Bown, 2019).